The Optimization of Selection and Planning Criteria for the Antarctic Protected Areas - Fedchuk, A. P. (Ukrainian Antarctic Journal, 2018)
The Aim of this piece of research is to generalize the best practices of applying selection criteria, principles and priorities, identified under the legal regime of the Antarctic Treaty System, as well as the development on scientific basis the ways of optimize the further expanding an effective and representative system of the Antarctic Protected Areas. Methodology. The comparative legal method and method of interpretation of the legal norms for the analysis of international legal acts, which form the current environmental regime of the region, have been applied. Additional analysis of the reporting, working and informational materials submitted at the annual Antarctic Treaty Consultative Meetings, and their working body – the Committee on Environmental Protection, have been made. Results. The definitions of the concept of protected areas in the international and regional contexts, the task and principles of spatial protection and management of the terrestrial and marine environment within the Antarctic Treaty Area are analyzed. The selection criteria of possible protected areas within different categories, as well as environmental risk assessment and feasibility criteria for assessment of possible protected areas are systematized as well. It is shown that further optimization of the development the protected areas network should be carried out by the mean of systematic conservation planning, which allows creating a comprehensive and scientific based regime of complementary areas of special protection and management with the provision of three key principles for area design – comprehensiveness, representativeness, and adequacy. The comprehensiveness means coverage of the both terrestrial and marine environments, as well as areas affected by anthropogenic impact and pristine areas. The representativeness is based on the results of environmental and biogeographical regionalization with the best available spatial data on regional biodiversity. Finally, the adequacy mean the designation the most appropriate category of the area meet the specified environmental objectives – from implementing strict protection, to the definition of multiple-use areas, or the spatial management of specific activities (e.g. fisheries or tourist activities) based on adaptive zoning tools, as well as ecosystem-based management. Conclusions. Obtained conclusions and recommendations could be served as a ground for systematic conservation planning process of designation an effective and comprehensive system of spatial protection and management throughout the whole region of Ukrainian scientific interests in Antarctica.